Pressure pain sensitivity: A new method of stress measurement in patients with ischemic heart disease. (August 2013) - Bergmann, Natasha; Ballegaard, Søren; Holmager, Pernille; Kristiansen, Jesper; Gyntelberg, Finn; Andersen, Lars J.; Hjalmarson, Åke; Bech, Per; Arendt-Nielsen, Lars; Faber, Jens
Abstract Background. Chronic stress is prevalent in patients with ischemic heart disease (IHD) and worsens the long-term prognosis. Chronic stress is vaguely defined, but is associated with depressive symptoms, reduced psychological wellbeing, and reduced quality of life (QOL). Stress seems to induce hyperalgesia.The aim of the present study was to evaluate hyperalgesia by pressure pain sensitivity (PPS) in patients with IHD, and compare PPS to questionnaires measuring depressive symptoms, reduced psychological wellbeing, and QOL as markers of stress. Design. A cross-sectional study of 361 subjects with IHD. Methods. PPS was measured on the sternum, and compared to the questionnaires: Clinical stress symptoms score (CSS), Major Depression Inventory (MDI), WHO-5 Wellbeing Index, and SF-36 QOL score. Results. PPS correlated to CSS (r = 0.20, p < 0.001), MDI (r = 0.14, p = 0.02), SF-36 mental component summary score (MCS) (r = − 0.10, p = 0.049), SF-36 physical component summary score (PCS) (r = − 0.17, p = 0.001), and self-perceived stress level (r = 0.15, p = 0.006). CSS correlated similarly (r = 0.5–0.7, all p < 0.001). Comparing subjects within the lowest vs. highest tertiles of PPS and CSS, the mean MDI score was 4 vs. 15, WHO-5 was 77 vs. 53, SF-36 PCS was 53 vs. 43, and SF-36 MCS was 58 vs. 46; all p < 0.001. Conclusions. PPS reflected to a modest degree markers of chronic stress in IHD. PPS and CSS together might be useful as easy-to use tools for evaluating these markers in IHD patients.